On a Simple Technique to Measure the Airborne Noise in a Motor Vehicle using Source Substitution - Putra, Azma (2011)
From various methods of measuring noise of a motor vehicle, there is a lack application on how to obtain the ‘pure’ airborne noise in a vehicle cabin as an important measure to improve the noise control treatment. This project proposes a technique in separating airborne and structure-borne noise in a motor vehicle using sound source substitution method. A cone loudspeaker was used as the substitution source and the overall transmission loss was measured to achieve this purpose. It is found that the structure-borne noise is dominant at low frequencies and airborne noise dominates at high frequency. The intersection frequency between the two is roughly 400 Hz.